Early season applications of fungicides to control diseases in winter wheat - Rich, Jonathan K. (Kansas State University, 2009)
Reducing plant disease pressure in wheat (Triticum aestivum L.) is an important management goal for producers. Over the last 10 years, steadily increasing adoption of no-till management has resulted in both over wintering as well as increased inocula levels for many diseases associated with straw residue. Reduced rates of fungicide, applied at early stages of plant development were investigated to measure their effect on reducing inocula density, controlling disease pressure and ultimately increasing grain yield in both no-till and conventionally planted wheat in Kansas from 2004-2008. Different cultivars were chosen based upon their resistance or susceptibility to specific diseases. The main diseases of interest were leaf rust (Puccinia triticina), speckled leaf blotch (Septoria triticii), tan spot (Pyrenophora tritici-repentis), and powdery mildew (Blumeria graminis (DC.) E.O. Speer f.sp. tritici). Two different studies were conducted. In 2004-2007, studies focused on the impact of spraying 133g/ha, half the normal rate, of propiconazole at Feekes 4.0. Disease levels and grain yields were evaluated. In 2008, four fungicide treatments and six cultivars were evaluated at 6 locations. Grain yield, measurements of green leaf duration, and grain yield components were also evaluated. No statistical differences were found in the 2004-2006 studies, but trends were apparent with grain yield increasing by 10.9%. The 2006-2007 growing season was a failure due to a late spring freeze. In the 2007-2008 growing season, statistically different grain yields were observed among some cultivars at two locations. At Partridge, KS and Salina, KS, Jagalene treated with an early-season application of propiconazole yielded significantly more than the untreated check, providing 11.4% and 9.5% increases, respectively. Early fungicide treatments also increased green leaf duration and reduced disease pressure. Further, larger scale studies need to be conducted to more accurate quantify the benefits of early applications of fungicides.
Keywords: Fungicides in wheat; Agriculture, Agronomy (0285)